2014
DOI: 10.1016/j.tcb.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A CULLINary ride across the secretory pathway: more than just secretion

Abstract: Mulitmeric cullin-RING ubiquitin ligases (CRLs) represent the largest class of ubiquitin ligases in eukaryotes. However, most CRL ubiquitylation pathways remain uncharacterized. CRLs control a myriad of functions by catalyzing mono- or poly-ubiquitylation of target proteins. Recently, novel CRLs have been identified along the secretory pathway where they modify substrates involved in diverse cellular processes such as vesicle coat assembly and cell cycle progression. This review discusses our current understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 114 publications
(163 reference statements)
2
27
0
Order By: Relevance
“…Nonetheless, the protein content of exosomes derived from both groups of cells was associated with the Notch cellular pathway (Supporting Information Table 3). We also observed the presence of the protein ubiquitin in both exosome extracts, a molecule related to protein sorting to exosomes (Supporting Information Table 2) .…”
Section: Resultsmentioning
confidence: 80%
“…Nonetheless, the protein content of exosomes derived from both groups of cells was associated with the Notch cellular pathway (Supporting Information Table 3). We also observed the presence of the protein ubiquitin in both exosome extracts, a molecule related to protein sorting to exosomes (Supporting Information Table 2) .…”
Section: Resultsmentioning
confidence: 80%
“…One of the positive clones isolated by the screening was Cul7. Cul7 serves as the scaffold protein that brings together the adaptor protein Skp1, the substrate-targeting subunit Fbw8, and the really interesting (RING)-domain protein ROC1 to form a cullin RING E3 ubiquitin ligase complex2728.…”
Section: Resultsmentioning
confidence: 99%
“…To further address the potential physiological and pathological roles of Eag channels in the mammalian brain, herein we aim to ascertain the protein degradation mechanism of rat Eag1 (rEag1) proteins. We have identified cullin 7 (Cul7), a member of the cullin-based E3 ubiquitin ligase family2728, as a potential binding partner of rEag1. By employing biochemical, morphological, and electrophysiological methods to characterize this novel protein interaction between Cul7 and rEag1, we conclude that Cul7 plays an important role in the molecular machinery dictating the ubiquitin-dependent regulation of rEag1 K + channels in both the ER and the plasma membrane.…”
mentioning
confidence: 99%
“…TNF-α is then secreted into the extracellular space or remains inside the cells in the form of secretary vesicles. Studies of other intracellular vesicles have shown that the destination of these vesicles is regulated by ubiquitination at their cytoplasmic surface [35] . It is conceivable that the miR-124-mediated decrease of USP2 and USP14 resulted in increased ubiquitination of vesicle protein(s), which perhaps led to fusion of the vesicles with lysosomes and degradation of TNF-α.…”
Section: Discussionmentioning
confidence: 99%